A retrospective study of irreversible electroporation for tumors adjacent to perihepatic important structure - Gong, Ju; Wang, Shunhong; Wang, Shuting; Li, Chaojie; Li, Wenhua; Chen, Yingjie; Xia, Ning; Wang, Chen; Wang, Zhongmin (Frontiers in Oncology, 2024)
BackgroundIrreversible electroporation has been proved as a feasible and safe method against tumor in liver. However, few studies focused on tumors adjacent to perihepatic important structure like vessels, biliary system and gall bladder. These structures limit the effectiveness of conventional treatments. The aim of this article is to analyze the clinical outcomes of patients with hepatic tumors at the special sites who received IRE treatment and provide reliable evidence for broadening the scope of IRE’s clinical application.MethodsThe clinical information of patients who underwent IRE ablation for tumors adjacent to perihepatic important structure between February 2017 and December 2021 was collected and retrospectively analyzed. All patients underwent contrast-enhanced CT or MRI for further evaluation at the 1-month follow-up and every 3 months thereafter. Post-ablation complications, recurrence, progression-free survival and overall survival were evaluated to analyze the prognosis of IRE ablation adjacent to perihepatic important structure. Categorical variables are presented as numbers followed by percentages. Continuous data are presented as the mean ± deviation. The tumor size and IRE ablation size were evaluated by the maximum diameters.ResultsThirty-two patients who underwent IRE ablation for tumor adjacent to perihepatic important structure were studied in this research. There were 39 lesions in 32 patients treated with IRE ablation. Fourteen of them (35.9%) were located adjacent to the porta hepatis, and 8 of them (20.5%) were located adjacent to the hepatocaval confluence. Subcapsular lesions accounted for 15.4% (6 of 39 lesions). The other 11 lesions were in the para gallbladder (5 of 39 lesions, 12.8%), the caudate lobe (5 of 39 lesions, 12.8%) and the colonic hepatic flexure (1 of 39 lesions, 2.6%). According to the Clavien−Dindo classification system for complications, all relative patients with cancer experienced complications below class III except one patient who developed postoperative hemorrhagic shock and improved after timely treatment. Recurrence in situ was observed in 5 of 32 (15.6%) patients. The median PFS of the patients who received IRE ablation was 384 days, and the median OS was 571 days.ConclusionIRE ablation is a feasible and safe treatment strategy for tumors adjacent to perihepatic important structure. With improved equipment, optimized therapeutic parameters and long-term clinical trials, IRE will play an increasingly important role in the treatment of tumors in liver.